Pengaruh Social Media Marketing, Kualitas Produk dan Citra Merek Terhadap Keputusan Pembelian Smartphone Realme di Kabupaten Bima - Mawardin; Amirulmukminin; M.Rimawan (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2024)
The research objectives are to find out and analyze the influence of social media marketing on realme smartphone purchasing decisions in Bima Regency, to find out and analyze the influence of product quality on realme smartphone purchasing decisions in Bima Regency, to find out and analyze the influence of brand image on realme smartphone purchasing decisions in Bima Regency, to find out and analyze the influence of social media marketing, product quality and brand image on realme smartphone purchasing decisions in Bima Regency. This research is causal associative research, the data analysis of this research uses a quantitative approach, the instrument in this research uses a questionnaire with a Likert scale, the data analysis technique uses the SPSS 26 application. Based on the research results, it can be concluded that social media marketing does not have a significant effect on decisions. purchasing a realme smartphone in Bima district, product quality has a significant influence on the decision to purchase a realme smartphone in Bima district, brand image has a significant influence on the decision to purchase a realme smartphone in Bima district, social media marketing, product quality, and brand image have a significant influence on the decision to purchase a realme smartphone in Bima district.